2022
DOI: 10.21203/rs.3.rs-1975336/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Isolation, Identification and Pathogenic Effects of Trichoderma spp. from Auricularia auricula

Abstract: Auricularia auricula, one of the most important edible mushrooms, is affected heavily by Trichoderma. We collected the diseased samples from the main A.auricula cultivation regions to characterize the pathogen and study the effect of Trichoderma spp. on A.auricula species. We identified one Trichoderma species, T.pleuroticola, based on the internal transcribed spacer and morphology characteristics and two types of A.auricula strains, Heiwei 15 (HW 15) and Hei 29 (H 29) were tested in this work. The growth rate… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 23 publications
0
1
0
Order By: Relevance
“…Three T. pleuroticola strains (TTP) were isolated from contaminated artificial bed-log of Zha Shui black fungus (Auricularia auricula) in Zhashui County, Shaanxi Province, China, and their sequence homology comparison showed that the TTP was clustered under the same clade with T. pleuroticola (accession number: JQ040377.1, strain number: CQJB5015), the homology reached 100%, and combined with the morphological characteristics of TTP were identified again. The main metabolites produced by T. pleuroticola, such as esters, ketones volatile organic compounds, amino acids and their derivatives, have antifungal activities, which may inhibit the mycelia growth of Auricularia auricula (Kong, 2022). A strain ZJ-03 isolated from oyster mushroom culture medium, identified by combining morphological observation and molecular biology as the T. pleuroticola, and producting xylanase activity above 3,000 IU/g (Qian et al, 2020), which considered an important source of xylanase production (Korkmaz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Three T. pleuroticola strains (TTP) were isolated from contaminated artificial bed-log of Zha Shui black fungus (Auricularia auricula) in Zhashui County, Shaanxi Province, China, and their sequence homology comparison showed that the TTP was clustered under the same clade with T. pleuroticola (accession number: JQ040377.1, strain number: CQJB5015), the homology reached 100%, and combined with the morphological characteristics of TTP were identified again. The main metabolites produced by T. pleuroticola, such as esters, ketones volatile organic compounds, amino acids and their derivatives, have antifungal activities, which may inhibit the mycelia growth of Auricularia auricula (Kong, 2022). A strain ZJ-03 isolated from oyster mushroom culture medium, identified by combining morphological observation and molecular biology as the T. pleuroticola, and producting xylanase activity above 3,000 IU/g (Qian et al, 2020), which considered an important source of xylanase production (Korkmaz et al, 2017).…”
Section: Introductionmentioning
confidence: 99%